To the Ramparts of Infinity : Colonel W. C. Falkner and the Ripley Railroad - Elliott, Jack D., Jr., 1953- (Book collections on Project MUSE., 2022)
"Before William Faulkner, there was Colonel William C. Falkner (1825-1889), the great-grandfather of the prominent and well-known Mississippi writer. The first biography of Falkner was a dissertation by the late Donald Duclos, which was completed in 1961, and while Faulkner scholars have briefly touched on the life of the Colonel due to his influence on the writer's work and life, there have been no new biographies dedicated to Falkner until now. To the Ramparts of Infinity: Colonel W. C. Falkner and the Ripley Railroad seeks to fill this gap in scholarship and Mississippi history by providing a biography of the Colonel, sketching out the cultural landscape of Ripley, Mississippi, and alluding to Falkner's influence on his great-grandson's Yoknapatawpha cycle of stories. While the primary thrust of the narrative is to provide a sound biography on Falkner, author Jack D. Elliott Jr. also seeks to identify sites in Ripley that were associated with the Colonel and his family. This is accomplished in part within the main narrative, but the sites are specifically focused on, summarized, and organized into an appendix entitled "A Field Guide to Colonel Falkner's Ripley." There, the sites are listed along with old and contemporary photographs of buildings. Maps of the area, plotting military action as well as the railroads, are also included, providing essential material for readers to understand the geographical background of the area in this period of Mississippi history"--